FUNGSI HUKUM ADMINISTRASI DALAM MEWUJUDKAN TATA KELOLA KEUANGAN DAERAH YANG BAIK - Anandy, Widyatmi (Universitas Tadulako, 2020)
In the management of regional finances often occurs management that is not in accordance with the procedure and substantially there has been abuse of authority by officials who have authority in the field of regional financial management resulting in local financial management cannot be accounted for. Based on this, the author propose the problem of how is the normative function af administrative law in local financial governance that includes planning, implementation, administration and accountability area. This research aims to analyze the extent to which the normative function of administrative law can realize good local financial governance. The research result indicate that if the normative function of administrative law which includes the aspects of authority, procedures and substances in the field of management of regional goodness that is in accordance with the legislation, the principle of governance, and the principles of financial management, both can realized. In order to realize it, then it needs to strengthen in the field of legislation related to the management of regional finances and consistent in its implementation.Keywords: Normative Function, Administrative law, and Local Financial